Epidemiology of lesions in high-level competition judo - Zinzen, E.; Vanbergen, J.; Clarys, P.; Ritchy, F.; Croisier, J.-L. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Judo means « the soft way », but is in the western countries evolved in a real high-level competition sport where performance and victory are the key issues. One of the consequences is that the top judo athletes suffer from a wide range of lesions. The purpose of this study was to make an inventory of these different lesions and study if there is a link between the lesions and: - the preferred technique of the competitors, - their preparation before the competition season (e.g. extreme weight loss, …. ) - their rehabilitation of previous lesions. Methods Data were gathered using a questionnaire on high-level judo (minimum junior = 17 years old) competitors. High level was defined as having at least a medal on the Belgian championships up to a medal on the last Olympics. Judokas of different countries (Belgium, France, Luxemburg, Switzerland, Holland and England) were questioned in their own language. The questionnaire was taken in the form of an interview. Data were firstly treated in a descriptive way, Spearman correlations were calculated and one-way ANOVA or Chi-square tests were performed where appropriate. The significance level was set on 5% It was found that lesions in the shoulder, knee and ankle region were the most frequent. Problems of the ligaments (sprains) were largely dominant. The tactical element seems to play a minor role in the development of the lesions but the way that judoka`s loose weight (to perform in their own or even a lower weight category) clearly increases the risk on lesions. The questionnaire also revealed that lesions are often badly or not treated since judo competition is performed in a linear way, meaning that one has each time to achieve medals on lower level competitions to be accepted to the higher level. A lesion on a lower level competition can therefore ruin a complete season. That is why a lot of athletes choose to ignore (as far as possible) the lesion. Medical and physiotherapeutic guidance during the training sessions of the athletes is thereby restricted to a minimum often again resulting in neglecting, underestimating and not treating different small traumata. Because improper rehabilitation of a minor lesion frequently precedes a far more disabling injury, such a situation appears unbearable in high level athlete management. Discussion/Conclusion Top level judoka`s are mainly suffering of sprains in the shoulder, knee and ankle region often due to ignoring (micro) traumata occurring during the training sessions. Their resistance is often compromised during competitions due to dehydratation aimed to loose weight. It is therefore suggested that further research should be done in a healthy weight control of top-judoka`s, that the concept of the judo competition should be revisited and that the medical and physiotherapeutic guidance of the top-athletes should be improved especially during the training sessions.